Four Blind Mice - Patterson, James (Alex Cross series;, 2011)
With his resignation from the Washington Police interrupted by a case involving a friend who has been framed for murder, Alex Cross and partner John Sampson journey across military lines to confront the most brutal killer of their careers. Alex Cross is plunged into a case where military codes of honor conceal dark currents of revenge and ambition, and the men controlling the moves have the best weapons and training the world can offer.